Antepartum depression and its predictors among pregnant adolescents in the northern part of Nigeria - Queen E. Adeyemo; Olubukola A. Adesina; Temitope Ilori; Isaac Olufadewa; Olayemi O. Oladapo; Olabanji T. Balogun; Zakka Musa; Blessing J. Adeyemo (International Journal Of Community Medicine And Public Health, 2026)
Background: Antepartum depression is a major public health issue, particularly among adolescents in low and middle-income countries, where early marriage and limited education are common. Although the religious and cultural beliefs in northern Nigeria concerning early marriage are common knowledge which prompted this study. Information on the predictors and prevalence of antepartum depression is limited. The study aimed to determine the prevalence and predictors of antepartum depression among pregnant adolescents in Kaduna state, north-western part of Nigeria. Methods: A cross-sectional design was used. Data was collected using a structured interviewer administered questionnaire among 349 pregnant adolescents attending antenatal clinics at six selected health facilities from January to May 2019. Depression was screened using the Edinburgh post-natal depression scale (EPDS≥13). Data were analysed using descriptive statistics, means and percentages, and logistic regression was used for predictors of antepartum depression. P value was set at